38. Defining a Theological Education Community - Palka, John (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
The current paper builds on Reports #34 and 35 in this series, which discussed the use of collaborative software to develop online communities in distance education (DE). The paper illustrates the manner in which an educational community's needs should be carefully examined, in the process of designing techniques that fulfill these needs at a distance. Student perceptions of their theological education community at Concordia Seminary, St. Louis, Missouri (http://www.csl.edu/Home.html) are investigated, via a survey instrument designed to define the students' communal needs.